Jung (Guerra) Nella Yerra Dei Musaheddin - Vendemmiati, Alberto; Lazzaretti, Fabrizio (Italy : Karousel Films, 2000)
’Jung’ means war in the language of the Dari, who consider war to be the very essence of life. This narrative documentary follows the quest of a surgeon who wants to establish an emergency hospital for civilian war victims in Afghanistan and is accompanied by an old correspondent who has reported there ever since the Soviet invasion. A deeply human story set against the backdrop of an endless war that has been forgotten by everyone except its victims.
Duration: 01:54:00
Keywords: Documentary films